Planck on Extragalactic Radio Sources: Data and Findings. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Partridge, Bruce; ,
Abstract: Planck scanned the entire sky every six months at nine frequencies bands from 28 to 857 GHz with enough sensitivity to detect over a thousand radio sources. It thus provided measurements of the mm and sub-mm spectra of these sources in a regular cadence, even at wavelengths hard to observe from the ground. Polarization measurements (or upper limits) are provided for brighter sources at 28-353 GHz. Finally, Planck is calibrated to <1% accuracy in most of its frequency bands. I briefly introduce the valuable data set Planck provides on extragalactic sources, then describe some of the scientific conclusions drawn from the Planck measurements.